Breastfeeding Assessment Score, Can it be used effectively in Thai population? - Podjanee Phadungkiatwattana; Pawinee Prewma (The Royal Thai College of Obstetricians and Gynaecologists, 2012)
Objective:To evaluate the effectiveness of the breastfeeding assessment score (BAS) in a Thai population to identify mothers who early stop exclusive breastfeeding in order to target early nursing interventions to encourage and support continued breastfeeding.Material and Methods: From September 2010 to May 2011, this diagnostic test including an interview for BAS variables was collected from mothers prior to hospital discharge at postpartum ward and follow-up phone calls at 10 days postpartum. The sample size calculations were nine hundred and fifty eight mothers. Results:Eight hundred and seventy eight mothers were enrolled in the study. The breastfeeding rate at 10 day of birth was 72.2%. Only 4 score variables (maternal age, previous breastfeeding experience, latching difficulty and breastfeeding interval) were statistically significant. The result could demonstrate an inverse correlation between the breastfeeding assessment score and the rate of cessation of breastfeeding at 10 days of age, likewise previous studies. The optimal cut-off score 8 showed a sensitivity of 53.7% and a specificity of 55.8 % to predict early cessation rate. The area under the ROC curve was 0.575. Conclusions: In Thailand, a breastfeeding assessment score may not clinically effective in predicting early cessation of exclusive of breastfeeding then development of other new assessment system is necessary.